Publishing student scholarship: exploring the ETD initiative at a medium-sized institution. Issue 4 (10th November 2014) - Wang, Xiaocan (Lucy); Bulick, Natalie; Muyumba, Valentine
Abstract : Purpose: – The purpose of this paper is to describe the Electronic Theses and Dissertations program implemented and managed by the Indiana State University since 2009. The paper illustrates issues relating to the background, policies, platform, workflow and cataloging, as well as the publication and preservation of graduate scholarship. Design/methodology/approach: – The authors examined many aspects of the Electronic Theses and Dissertations program and addressed issues dealt before, during and after the publication of the electronic theses and dissertations collection. The approaches the authors utilized are literature review and personal management experience from working on the program. Findings: – Implementing an Electronic Theses and Dissertations program involves providing a series of management services. These services include developing relevant policies, implementing an archiving and publication platform and creating submission and publishing workflows, as well as cataloging, disseminating and preserving the student collection. Openly publishing the collection through a range of access points significantly increases its visibility and accessibility. Adopting several archival and preservation strategies ensures the long-term readiness of the collection. Originality/value: – This paper will provide useful practices for implementing an ETD program to those institutions new to the ETD initiative process. It also contributes to the current body of literature and to the overall improvement of ETD programs globally.